2020
DOI: 10.1515/jag-2019-0046
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Msplit estimates in the context of vertical displacement analysis

Abstract: This paper concerns two types of Msplit estimation: squared Msplit estimation (SMS), which assumes normality of observation errors and absolute Msplit estimation (AMS), which applies {\text{L}_{1}} norm criterion. The main objective of the paper is to assess the accuracy of such estimators in vertical displacement analysis by applying Monte Carlo simulations. Another issue is to compare the accuracy of both estimators with the accuracy of the least squares estimation (LS). The paper shows that the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Both types of iterative processes require a proper choice of starting points [43], and they should both be stopped for such a j = k for which [29,34]. Previous papers [34,35,43] showed that differences in the SMS and AMS estimations' objective functions also result in slightly different general properties. As was shown, both methods' weight functions differ from each other, which leads to the necessity of two different iterative processes.…”
Section: Theoretical Foundations Of M Split Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both types of iterative processes require a proper choice of starting points [43], and they should both be stopped for such a j = k for which [29,34]. Previous papers [34,35,43] showed that differences in the SMS and AMS estimations' objective functions also result in slightly different general properties. As was shown, both methods' weight functions differ from each other, which leads to the necessity of two different iterative processes.…”
Section: Theoretical Foundations Of M Split Estimationmentioning
confidence: 99%
“…Applications of M split estimation concerned so far not only processing of TLS data (presented in [1,15,22,31]) but also deformation analyses [29,30,[32][33][34][35][36], direct identification of gross errors [37], linear regression analyses [30,34], robust coordinate transformation [38], S-transformation [39] and marine navigation [40]. Most of these applications applied only the squared M split estimation (SMS), of which the objective functions stem from the assumption that observation errors are normally distributed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next application of the Msplit method was as an estimation method in the context of the analysis of the vertical displacement of geodetic points [24] or for detecting circular objects in a point cloud [25].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas AMS estimation gives correct results (all biases close to 0) only for negative values of ∆H A or when ∆H A > 40 mm. It is caused by a coincidence of some ∆H A with value of ∆H B = 20 mm and with the gross error (Wyszkowska and Duchnowski, 2020). On the other hand, the biases of ∆Ĥ A and ∆Ĥ B for AMS estimation are of small magnitude.…”
mentioning
confidence: 95%